General Practitioners’ Perspective towards Healthy Ageing in Indonesia - Ray Wagiu Basrowi; Tonny Sundjaya; Deni Krisnamurti; Bertri Maulidya Masita (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: The rapid ageing population among older adults from 2020 to 2040 has led to an emerging focus as this group begins to experience ageing and has a higher risk of having chronic illness of non-communicable diseases. Therefore, it is important to provide General Practitioners (GPs) with adequate knowledge and attitude of healthy ageing to ensure the quality of health service among older adults.Objectives: To identify the perspective of general practitioners including the knowledge, attitude and practice towards adult health and nutrition to support healthy ageing in Indonesia.Methods: An online survey was conducted among 100 general practitioners registered at the Indonesian Medical Council (KKI) and domiciled in the Greater Jakarta area and outside the Jabodetabek area. The sample recruitment process was carried out using the Alomedika online application. All data were analyzed using SPSS software.Results: Almost all (92%) of respondents who took this survey had a supportive attitude in providing additional nutrition to adults to support healthy ageing. About 76% of the respondents did so by recommending milk. However, in terms of knowledge, around 67% of the respondents showed inadequate results, especially about physiological changes that occurred in adults. There is no statistically significant difference between respondents’ demographic characteristics and all perspectives measured in this study (i.e., knowledge, attitude and practice)Conclusions: The study indicates that it is important to educate general practitioners about the healthy aging process in order to maintain general practitioners' attitudes and behavior in health services to support the success of achieving healthy aging in Indonesia.